STUDYING THE INFLUENCE OF ENVIRONMENTAL FACTORS ON EYE DISEASES - Rasulova Nilufar; Azamatova Fazilat (Scholars Digest Publishing, 2024)
Eye diseases are one of the leading causes of visual impairment and blindness throughout the world. Environmental factors such as air pollution, ultraviolet (UV) radiation exposure, climate conditions and lifestyle choices play a key role in the development of a number of eye diseases, including cataracts, glaucoma, macular degeneration and dry eye syndrome. This article examines the influence of various environmental factors on the development of eye diseases and emphasizes the importance of prevention and protection of vision. Modern research in this area is also reviewed and measures are proposed to reduce the negative impact of the environment on eye health.
Keywords: Environmental factors, eye diseases, cataracts, glaucoma, macular degeneration, dry eye syndrome, UV radiation, air pollution, prevention. Key words: Environmental factors, eye diseases, cataracts, glaucoma, macular degeneration, dry eye syndrome, UV radiation, air pollution, prevention.